Problems of labor uberization and its debates in Brazil and around the world, with a focus on legal implications (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article critically examines the phenomenon of labor uberization, focusing on the Brazilian reality and its legal implications. It first distinguishes uberization from other precarious labor models such as crowdwork, freelancing, and hiring as a legal entity. Then, it shows the historical and social context of Uber’s expansion in Brazil. The article evaluates both the advantages and disadvantages of this work model, highlighting the illusion of flexibility in contrast with the lack of labor guarantees. The legal analysis addresses core issues such as remuneration, employment relationship, rest time, and social security. Finally, it compares international legal approaches — particularly from Europe and the United States — emphasizing the urgent need for Brazilian regulation, including a discussion of Draft Law 12/2024 and discuss what should be done in the national scenario.